1971
DOI: 10.1203/00006450-197111000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Erythrocyte Sodium Flux in the Pathophysiology and Genetic Expression of Hereditary Spherocytosis

Abstract: ExtractErythrocyte sodium transport was studied in five families of patients with hereditary spheroeytosis (HS). Values for ouabain-insensitive sodium efilux in the group with HS (mean = 19.9% of cellular sodium-22/hr, so = ±2.7) were significantly greater (P < 0.001) than those found in the normal group (mean = 13.8%, SD = ±2.7). No clinical evidence of HS was found in the parents; however, 4 of the 10 parents had ouabain-insensitive erythrocyte sodium-22 efilux rates in the HS range in comparison to 3 of 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1974
1974
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Several studies have shown that the erythrocyte "permeability" to sodium and potassium is increased in HS and that the increased sodium permeability is associated with increased activity of the Na-K ATPase. [7][8][9][10][11][12] It has been postulated that the associated increase in adenosine triphosphate (ATP) consumption leads to ATP depletion during erythrostasis, followed by increased calcium entry, activation of the Gardos channel, and dehydration. 8,13 A more recent study found no changes in the transport activity of Na-K-2Cl cotransport and Na/Li exchange in human HS erythrocytes, whereas sodium potassium pump activity was increased and potassium chloride cotransport activity was decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the erythrocyte "permeability" to sodium and potassium is increased in HS and that the increased sodium permeability is associated with increased activity of the Na-K ATPase. [7][8][9][10][11][12] It has been postulated that the associated increase in adenosine triphosphate (ATP) consumption leads to ATP depletion during erythrostasis, followed by increased calcium entry, activation of the Gardos channel, and dehydration. 8,13 A more recent study found no changes in the transport activity of Na-K-2Cl cotransport and Na/Li exchange in human HS erythrocytes, whereas sodium potassium pump activity was increased and potassium chloride cotransport activity was decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Hereditary spherocytosis (HS) is a common inherited RBC membrane defect associated with haemolytic anaemia and heterogeneous inheritance and clinical presentation [13,14,15]. One distinguishing characteristic of HS is the presence of circulating dense and dehydrated spherocytes that are intrinsically leaky to sodium [15,16,17,18,19]. Up to now, increased membrane passive permeability to cations has been reported for the spherocytic (sph) RBCs in several animals [20] and only a few cases of HS have been examined for defects in the various components of the ouabain-resistant pathways [20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%